Enhancing hydrogen adsorption through optimized magnesium dispersion on fibrous nano-silica scaffold: Kinetic and thermodynamic studies - Abdulkadir, B. A.; M., Ismail; Herma Dina, Setiabudi (Elsevier Ltd, 2024)
Silica material, particularly, fibrous nano-silica (FNS) is one of the potential scaffolds for hydrogen storage, however, low hydrogen adsorption limits its application. To improve its adsorption capacities, the incorporation of active metal, particularly magnesium (Mg), was prepared. FNS with well-developed pore structures and a good surface area were synthesized. Various amounts of Mg (1–5 wt%) were infiltrated into the FNS. To study the effect of metal loading, the adsorbents were characterized by their chemical structure, crystal phase, morphology/elemental composition, and textural properties. Subsequently, hydrogen adsorption studies were conducted where different reaction conditions, including metal loading, catalyst loading, and temperature were studied. Furthermore, kinetic and thermodynamic studies were conducted based on the Langmuir and Van't Hoff models. The results of the characterizations show that the Mg metal was well dispersed into the porous FNS with no significant changes in the original structure. The optimum adsorption of 1.90 wt% was achieved at 1.0 wt% Mg loading, 0.1 g catalyst loading, and 423 K temperature. Kinetic studies demonstrated that the adsorption process fits the pseudo-second-order reaction. The 1%Mg/FNS adsorbents showed good reusability where 5 runs were conducted with <5 % loss in activity. Therefore, this result indicated that infiltration of Mg into the silica is one of the most active approaches in improving the hydrogen adsorption capacities of FNS.